Islamic Elements of Plants Selection on Malay Landscape in Kota Bharu City, Kelantan, Malaysia. - Ramle, Abdullah; Nur Hafizah, Ramle; Ab. Aziz, S.; Mohd Sukhairi, Mat Rasat (2014)
Background: In this research, Islamic elements of plants selection on Malay Landscape in Kota Bharu city, Kelantan, Malaysia was accomplished. Islamic religion transferred to Tanah Melayu since long ago had conquered Malay society’s culture and surrounding. Objective: The nature of Islam can be compatible with a wide variety of cultures facilitate the acceptance of Islam in Tanah Melayu. Promulgation or preaching done by traders who come cause assimilation of Malay society. Assimilation of the culture of Islam that occurred in the Malay community greatly changed the pattern of life directly or indirectly, including the environment. Results: In the proceeding research in Kota Bharu city of Islam which is eagerly developed by Municipality Council of Kota Bharu (Majlis Perbandaran Kota Bharu), the attempt of inserting Islamic landscape motif in the city is under progress. Misinterpretation of Islam in understanding the landscape angle applied to the Kota Bharu city's landscape affect local cultural landscape. Consequently, these values have eroded local Malay traditional landscape. Application of floras species mostly from Middle East did change the environment of Malay landscape. Conclusion: Therefore, this research will view the Islamic elements of plant selection on Malay landscape to pin out crystal clear point of view of the values apprehension beside the ability to sustain Malay identity.